2017
DOI: 10.1007/s00436-017-5404-3
|View full text |Cite
|
Sign up to set email alerts
|

Whipworm diversity in West African rodents: a molecular approach and the description of Trichuris duplantieri n. sp. (Nematoda: Trichuridae)

Abstract: Whipworms were collected from rodents (Muridae) from six West African countries: Burkina-Faso, the Islamic Republic of Mauritania, and the Republics of Benin, Guinea, Mali and Senegal. Molecular sequences (ITS-1, 5.8S and ITS-2 of the ribosomal DNA gene) and morphometric characters were analysed in Trichuris (Nematoda: Trichuridae) specimens found in seven host species: Arvicanthis niloticus, Gerbilliscus gambianus, Gerbillus gerbillus, G. tarabuli, Mastomys erythroleucus, M. huberti and M. natalensis. Phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…No molecular information exists on previously reported specimens from SEA and Oriental Trichuris from rodents, but the clear morphological and metrical differences provide the first evidence of distinct species. As more species of Trichuris are described, additional molecular studies are necessary to avoid the shortfall of morphometrical characters to clearly distinguish different species [7,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No molecular information exists on previously reported specimens from SEA and Oriental Trichuris from rodents, but the clear morphological and metrical differences provide the first evidence of distinct species. As more species of Trichuris are described, additional molecular studies are necessary to avoid the shortfall of morphometrical characters to clearly distinguish different species [7,11].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, various studies have established molecular evidence that representative host species of Murinae (Apodemus, Mus and Rattus) sampled in several localities across Europe are associated with T. muris as a unique whipworm species [4,5,6]. This molecular evidence is of particular importance as morphometrical traits are not conclusive to distinguish Trichuris species from rodents [7] and other mammals (e.g. : [8]).…”
Section: Introductionmentioning
confidence: 99%
“…Each of these organs was then carefully cut open and the content was checked under a stereomicroscope. The helminths were identified to genus or species level using morphological characteristics (54,55).…”
Section: Parasitological Examinationmentioning
confidence: 99%
“…In this study, we used the multimammate mouse (Mastomys natalensis) as a model system to investigate how the hosts' age, sex, and behavior affect the individuals' infection risk, parasite load, and community structure of the different gastrointestinal helminths and how this, in turn, influences their viral infection history with a common arenavirus (Morogoro virus, MORV). Mastomys natalensis is the most common indigenous rodent in sub-Saharan African and host for a wide variety of parasites, such as several arenaviruses (41)(42)(43)(44)(45), plague bacteria (46), cutaneous leishmaniasis (47) as well as different ecto- (48,49) and endoparasites which have been studied extensively over the years (50)(51)(52)(53)(54)(55)(56)(57). They are therefore an excellent model system to study the interaction between behavior and parasitic communities, especially since it has been found that there are consistent differences in behavior among individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that the Mini-FLOTAC represents a reliable technique to detect the zoonotic S. mansoni and other parasites in rodent reservoirs. A growing body of information on helminth communities of West African rodents is gradually enhancing our understanding of host use and transmission dynamics [5557]. To date, the quantification of adult helminths during post-mortem examination remains the gold standard technique for assessing infection in wildlife; as a consequence, non-invasive methods are often untested or sporadically applied [9, 14].…”
Section: Discussionmentioning
confidence: 99%